Persepsi Remaja Desa Teluk Tamiang Terhadap Pelestarian Budaya Pesta Laut Mappanretasi di Era Modern - Lutfi Putri Kholfiyah; Yayah Khisbiyah (Jurnal Impresi Indonesia, 2025)
The cultural diversity that exists in Indonesia and is still preserved from generation to generation is a picture of Indonesia's richness, teenagers often perceive culture as something ancient. The purpose of this study is to find out how the perceptions of teenagers in Kotabaru towards the preservation of the Mappanretasi sea party culture in Teluk Tamiang Village and to find out what factors influence the perceptions of teenagers. The research method used was descriptive qualitative research with data collection techniques using snowball sampling techniques, in the form of interviews with 4 subjects namely WD, MI, HD, and IR as well as direct observations conducted in Teluk Tamiang Village. The results of data acquisition were then analyzed using thematic analysis techniques. Based on the results of the analysis conducted from interviews and observations, Mappanretasi activities are perceived as cultural activities that must be carried out continuously as a form of gratitude for the abundance of sustenance given by nature and as a repellent for reinforcements. The perceptions held by the subjects in this study were based on individual perceptions, Social Perceptions and Non-Social Perceptions.